Assessment of the Effectiveness of Healthcare Waste Management Practices in Major Town of Niger State, Nigeria - Abdullahi, Abdullahi, I; Busari, Busari, A.O; TANKO, J. A. TANKO (Journal of Environment, 2022)
Purpose: The study was to examine the healthcare waste management practices in Niger State, Nigeria, with a view of promoting the quality of environment. The study has the following objectives: Determine the factors which influenced healthcare waste management practices in Niger State, assess the problems hindering the provision of adequate healthcare waste management practices, examine the physical planning implications on their sustainability, and examine the existing waste-management practices vis-a-vis of GHG emissions mitigation mechanism. Methodology: A questionnaires survey was carried out on the one hundred and fifty (150) respondents who were workers in the health facilities selected for the study for proper assessment of healthcare waste management of the hospitals. There was an interview of the various heads of departments of the hospitals' administration to obtain accurate information on the management of the healthcare waste. Findings: The study found that the health facilities do not have records of the volume of waste which they generate. The medical wastes generated range from 0.116 to 0.561 kg/bed/day, but there is no standard gauge for measuring waste collected in Niger state. Thus, the average generation rate is approximately 0.181 kg/bed/day. What the study classified as general waste was found to be common among the health facilities in the study area. About 66.4% of the respondents ascertained this type of waste which constituted of paper, food and plastic. Unique Contribution to Theory, Policy and Practice: Policies and monitoring mechanisms should be generated and coordinated at the federal and State levels and including Local Governments Areas (LGA) and Health facilities levels